DYNAMICS AND CHALLENGES OF LEGAL PROTECTION IN DIGITAL BUSINESS TRANSACTIONS - Deswal Arief (RADJA PUBLIKA, 2025)
The rapid development of information technology has transformed business transaction patterns in Indonesia through e-commerce, fintech, and digital banking. While providing efficiency and accessibility, this digitalization poses significant legal challenges, particularly regarding the regulation of electronic contracts and consumer protection. Electronic contracts are recognized as valid under the ITE Law and the Civil Code, but practices for proving party identity, the validity of digital signatures, and return and refund mechanisms still create legal uncertainty. For consumers, default in e-commerce transactions, information asymmetry, and low legal literacy are key obstacles, while oversight of digital business actors and law enforcement are suboptimal. Regulatory gaps, including those concerning the protection of personal data and cross-border transactions, further reinforce the need for legal improvements. This study uses a normative juridical method with a statutory and conceptual approach, examining the ITE Law, the Consumer Protection Law, the Government Regulation on Electronic Transactions (PPPSTE), and relevant legal literature to analyze these dynamics and challenges. The results of the study indicate the need to update legal norms, strengthen oversight, and improve public digital and legal literacy to create a fair, safe, trustworthy, and sustainable digital business ecosystem in Indonesia.